Neuropsychiatric side reactions of leukotriene receptor antagonist, antihistamine, and inhaled corticosteroid: A real-world analysis of the Food and Drug Administration (FDA) Adverse Event Reporting System (FAERS) - Sainan Bian (Elsevier, 2021)
Background: There are limited real-world studies on the differences in leukotriene receptor antagonists (LTRA), H1-antihistamines (H1-AH), and inhaled corticosteroids (ICS) associated neuropsychiatric events. In this study, we aimed to analyze the characteristics of drug associated neuropsychiatric events, and compare the differences among different drug categories. Methods: Disproportionality analysis and Bayesian analysis were used in data mining to identify suspected neuropsychiatric events associated with LTRA, H1-AH, and ICS based on the United States Food and Drug Administration (FDA) Adverse Event Reporting System (FAERS) from January 2004 to September 2020. Demographic information, time interval to onset, and death rates of LTRA, H1-AH, and ICS-associated neuropsychiatric events were also analyzed. Results: A total of 9475 neuropsychiatric events were identified. The number of neuropsychiatric events related to LTRA, H1-AH, and ICS were 5201 (54.89%), 3226 (34.05%), and 1048 (11.06%), respectively. LTRA related neuropsychiatric events were more common in patients aged 4–6 years (18.66%). H1-AH and ICS related neuropsychiatric events were more common in patients aged 18–44 years (29.92%) and older than 65 years (30.60%), respectively. Montelukast was highly associated with neuropsychiatric events, with a high reporting odds ratio (ROR). Most neuropsychiatric symptoms occurred within the first 10 days after drug initiation (78.63% for LTRA, 91.39% for H1-AH, and 84.07% for ICS). The death rate due to neuropsychiatric events of first generation H1-AH was significantly higher than that of LTRA and ICS (p < 0.001). Conclusions: LTRA associated neuropsychiatric events reported in FAERS were most frequent in 4 to 6-year-old children. Most reported cases occurred within the first 10 days after drug initiation. The second generation H1-AH was relatively safe for neuropsychiatric events compared with the first generation. The fatality rate due to first generation H1-AH associated neuropsychiatric events was higher than that of LTRA and ICS. More attention should be paid to specific patients treated with LTRA and H1-AH.